2010
DOI: 10.4314/ajoh.v2i1-2.56995
|View full text |Cite
|
Sign up to set email alerts
|

Management of dental waste by practitioners in Nairobi, Kenya

Abstract: Objective: Dental wastes are material that has been utilized in dental clinics, which are no longer wanted for use and therefore discarded. Improper disposal of these dental wastes can cause harm to the dentist, the people in immediate vicinity of the dentist, waste handlers and general public and the environment through production of toxins or as by products of the destruction process. This study aims to determine the knowledge, attitudes and practice on management of dental wastes among dental practitioners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
3
11
0
1
Order By: Relevance
“…[13] The present study participants showed better awareness about BMW management as compared to dentists from Nairobi, Kenya where nearly half of them were unaware about guidelines for waste disposal. [14] In this study, the percentage of respondents using color-coding for disposal of waste was similar to the ones who had registered and had the license for BMW disposal. 108 (72%) dentist and 19 (33.9%) dental auxiliaries, were following color-coding system for the disposal of waste, whereas in a study done by Narang et al, 68 (85%) dental surgeons and 44 (55%) dental auxiliaries, were using color-coded bags for the waste disposal.…”
Section: Methodssupporting
confidence: 59%
“…[13] The present study participants showed better awareness about BMW management as compared to dentists from Nairobi, Kenya where nearly half of them were unaware about guidelines for waste disposal. [14] In this study, the percentage of respondents using color-coding for disposal of waste was similar to the ones who had registered and had the license for BMW disposal. 108 (72%) dentist and 19 (33.9%) dental auxiliaries, were following color-coding system for the disposal of waste, whereas in a study done by Narang et al, 68 (85%) dental surgeons and 44 (55%) dental auxiliaries, were using color-coded bags for the waste disposal.…”
Section: Methodssupporting
confidence: 59%
“…The term ‗clinical waste' is associated with waste originating from medical, dental and veterinary sources and has been defined as ‗waste that is contaminated with blood, saliva or any other bodily hazardous fluids and which may prove hazardous to any person coming into contact with it' (Department of Health, 1992). The World Health Organisation (WHO) has defined healthcare waste as ‗all waste produced by healthcare establishments, research facilities and laboratories including the waste originating from ‗minor' or ‗scattered' sources such as that produced in the course of healthcare undertaken in the home (such as dialysis and insulin injections)' (WHO, 1999) [4].…”
Section: Introductionmentioning
confidence: 99%
“…yaptığı çalışmada diş hekimlerinin %10,7'si tarafından amalgamın uygun olarak bertaraf edilmemesinin toksik etki oluşturduğu belirtilmiştir. 36 Dental uygulamalar sonucu oluşan amalgam atıklarının uygunsuz bertarafının oldukça yüksek olduğunu görmekteyiz. Bu durumun tespitinin güç olmasından, finansal yetersizlikten, kliniklere herhangi bir yaptırımının olmamasından ve en önemlisi amalgamın toksik etkileri hakkında bilgi eksikliğinden, atık yönetimine ilişkin hizmet içi eğitimlere gereken önemin verilmemesinden kaynaklandığı düşünülmektedir.…”
Section: Gereç Ve Yöntemlerunclassified